EXPLAINING ARTIFICIAL INTELLIGENCE IN EDUCATION: APPROACHES TO INTEGRATION IN AUTOMATED INFORMATION SYSTEMS: EXPLAINING ARTIFICIAL INTELLIGENCE IN EDUCATION: APPROACHES TO INTEGRATION IN AUTOMATED INFORMATION SYSTEMS - Ivanova, Desislava (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2025)
This paper provides a systematic review of approaches for integrating Explainable Artificial Intelligence (XAI) into educational Automated Information Systems (AIS). It categorizes XAI methods into post-hoc explanations, inherently interpretable models, hybrid approaches, and calibration/visualization techniques, analyzing their strengths, limitations, and applicability for tasks such as learner dropout prediction, early warning, and personalized mentoring. Practical examples illustrate the benefits and challenges of XAI adoption, including the trade-off between accuracy and interpretability, technical barriers, and privacy concerns. Future directions include role-adaptive explanations, visual and interactive interfaces, and standardized quality metrics for educational contexts.